AKIBAT HUKUM TERHADAP PERJANJIAN PERKAWINAN YANG DIBUAT SETELAH PERKAWINAN BERLANGSUNG - Padma Patmala Adi, Komang; Putrawan, Suatra (Kertha Semaya : Journal Ilmu Hukum, 2013)
This paper shall be entitled as “Legal Implication of Post-Marriage Pre-nuptial Agreement”. This paper shall apply normative legal research method combined with statutory approach in its composition. The purpose of this paper is to determine the regulation of the Pre-nuptial agreement and legal implication of post-marriage pre-nuptial agreement. Pre-nuptial agreement is regulated within the Law of Marriage and Family and the Civil Code. By laws, pre-nuptial agreement is composed in prior to the marriage, thus shall have its effect during the marriage. In contrast, should any pre-nuptial agreement failed to meet such requirement, the agreement shall be null and void.
Keywords: agreement, marriage, legal implication